Pendampingan Edukasi Generasi Muda dalam Menangkal Radikalisme Karena Keberagaman Budaya, Suku dan Agama di SMA Takhassus Al-Qur’an Nurul Islam Ngabang - Aminudin, Aminudin (Annusfy : Journal of Multidisciplinary Research, 2025)
This community outreach program aims to improve students' understanding of the dangers of radicalism, strengthen awareness of the importance of tolerance in multicultural life, and foster a moderate character based on the principles of rahmatan lil 'alamin (blessings for the universe) and the values ​​of Pancasila. The outreach program at SMA Takhassus Al-Qur'an Nurul Islam Ngabang involved a participatory and educational approach, encompassing problem identification, outreach, and activity evaluation. The results showed that students were able to understand the characteristics of radicalism, reject intolerant ideologies, and demonstrate mutual respect in cross-cultural and interfaith interactions. This outreach also successfully strengthened national commitment and a spirit of unity among students.